Investigation of small punch creep testing - Stoyanov, Miroslav (2013)
Assessing the damage level of in-service components and obtaining material properties for welded structures exposed to creep is essential for the safe operating of power generation industry. Standard creep testing techniques require relatively large volumes of material for the machining of testing samples. For that reason they are not usually suitable for obtaining creep properties of in-service structures. It has been found that significant amount of the failures in welds exposed to elevated temperatures occur in an area formed due to the complex thermal and cooling cycles during the welding process. Because of this a different approach is needed for the derivation of creep properties from small amounts of metal. The small punch creep testing method is considered to be a, potentially, powerful technique for obtaining creep and creep rupture properties of in-service welded components. However, relating small punch creep test data to the corresponding uniaxial creep data has not proved to be simple and a straightforward approach is required.